(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2022)
Historians can contribute significantly to education historiography to bolster education transformation. Contemporary scholarship in education, in the main, mostly wrestles with the current dispensation’s transformation of education policy endeavours in the post-apartheid era. While there is no substantial or insurmountable disagreement on the education policy objectives in post-apartheid South Africa, much of the contestations seem to arise from how these objectives should be realised to achieve their lofty ideals. This is where learning from history is important. History is not merely concerned with constructing knowledge through relooking the past but also attending to the “selection” and “silences” over time. Among other things, South Africa’s history also provides significant insights into how education contributed to developing a first-world economy in the country. This article argues that, because of education’s ability to enable social and economic mobility to affect families, communities, and society in general positively, education is a public good that requires historians’ involvement and attention. The article also considers the significance of funding education as a public good. Consequently, the paper argues that historians can make a significant contribution to transforming education in their continuous rewriting of history to learn from the past and foreground education as a public good in the past and present for the future.